(untitled) (Research, Society and Development, 2020)
The aim of this work was to describe the fishing of Centropomus undecimalis, in the Brazilian Amazonian coast, based on the knowledge of the fishing actors and to trace the socioeconomic profile of these workers. The data were obtained through semi-structured interviews with fishermen, masters and boat owners, between March and May 2019 in the municipality of Bragança (PA), using the snowball technique. The data were tabulated and analyzed using Microsoft Office Excel and Past Software. Tracing the socioeconomic profile of the interviewees based on age, education, acting time in fishing and income, it was observed that there was no significant difference between the participants, indicating a similar group, except in relation to income, which varied significantly according to occupation / profession. The fishing of C. undecimalis on the Amazon coast occurs mainly through artisanal vessels that vary from small to medium-sized and use essentially a mobile net of the fishery type that is normally used to catch “pescada-amarela”. They operate in fisheries near or far from the landing sites, popularly known as “Norte” (AP), “Emburateuas”, “Poços”, “Barra de Bragança” (PA) and the coastal portion of Maranhão (MA). The capture of this species is carried out throughout the year, although its production is low and irregular. However, it has high commercial value and good acceptance in the market, especially the national one. This low catch illuminates a warning signal about the stock status of this species and opens new lines of investigation with the hypothesis of the inadequacy of the fishing technique currently used in its capture.